Ultrasound-Assisted Ultra-Mild-Acid Hydrolisis of -Carrageenan - Ratnawati Ratnawati; Nita Indriyani (Reaktor, 2017)
The low molecular weight fraction of κ-carrageenan is useful in biomedical applications. An ultrasound-assisted acid hydrolysis of κ-carrageenan has been studied. κ-carrageenan with an initial number-average molecular weight of 629 kDa was dispersed in distilled water to form a 5 g/l solution. The pH (3 and 6) of the solution was adjusted by adding HCl solution. The depolymerization reaction was carried out in an ultrasonic device at various temperatures (30, 40, 50, and 60°C) and times (8, 16, 24, and 32 min). The experimental results showed that ultrasound positively contributed to acid hydrolysis process. The number-average molecular weight of the treated k-carrageenan was lower or the percentage of reduction was higher at lower pH, longer reaction time, and higher temperature. The lowest number-average molecular weight (14 kDa) or the highest percent of molecular weight reduction reduction (97.7%) was achieved after ultrasonic irradiation at 60°C and pH 3 for 32 min. Keywords: depolymerization; midpoint scission; ultrasonication